Penggunaan Antibiotik Pada Bangsal Mata RSUP Dr. M. Djamil Padang Tahun 2005 sampai dengan Tahun 2007 - Zet Rizal; Rostin Rostin; Helmi Arifin (STIFARM Padang, 2009)
Research about usage of antibiotic at Barn Eye of RSUP DR. M. Djamil Padang to year 2005 up to 2007. Result of obtained research pursuant to data of retrospective at cataract patient, pterigium, tumor and conjunctivitis show eye patient which is higher infection of year 2005 equal to 19.49 % year 2006 equal to 18.57 % year 2007 equal to 25.67 %. So that usage of high antibiotic also in the year 2005 equal to 47.37 %. year 2006 equal to 79.79 %. year 2007 equal to 45.26 %. Usage of antibiotic pursuant to precisely indication at disease of cataract, pterigium, tumor and conjunctivitis at precise eye patient 100 % in the year 2005 up to 2007. Precisely dose usage of antibiotic at cataract patient of pterigium, tumor and konjungtivitis at precise eye 100 % in the year 2005 up to 2007. Usage of correct antibiotic of patient, precise of drug, precise is way of wearing, at type medicines amoxicillin, chloramphenicol, and precise siprofloxacin 100 % in the year 2005 up to 2007. From result of interview obtained at patient which less than five day taken care of to get continuation recipe to go home.